Rulings on Harm and Its Rules in Islamic Fiqh (Revue El-Wahat pour les Recherches et les Etudes, 2025)
The evolution of life and the invention of machines have brought great benefits to humanity, saving effort and time. However, along with these advantages, they have also resulted in numerous and diverse harms. This raises the main research question: What are the legislative measures introduced by Islam, in terms of rulings and maxims, to address the issue of harm? The study aims to explore these rulings and maxims using a descriptive and analytical approach, structured into two main sections, each with its own subdivisions. The first section examines the rulings on harm in Islamic jurisprudence, while the second focuses on the legal maxims related to harm in Islamic law. The study concludes that Islamic law strictly prohibits causing harm to oneself or others by any means and mandates its removal once it occurs. This includes preventing its continuation, eliminating its effects, repairing the damage caused, and compensating for any deficiencies it creates.Keywords: Harm, Causing Harm, Rules, Rulings.